Case Series of Primary Testicular Lymphoma: Insights into a Rare Condition (Indian Journal of Case Reports, 2025)
Primary testicular lymphoma (PTL) is a rare extranodal type of non-Hodgkin’s lymphoma (NHL), accounting for <5% of testicular malignancies and 1–2% of NHL cases. The most common PTL is diffuse large B-cell lymphoma (DLBCL) type, a highly heterogeneous form of NHL, with a higher incidence in men over 60. Testicular lymphoma frequently recurs in extranodal sites, especially the contralateral testis and central nervous system (CNS), which is a sign of poor prognosis. Given the aggressive nature of testicular DLBCL, multimodal management is required, including orchiectomy, immunochemotherapy with rituximab, contralateral testicular radiation, and CNS prophylaxis to improve outcomes. In this case series, we present two cases of PTL, both diagnosed through histopathology and imaging and treated with a combination of surgery, chemotherapy, and radiation therapy.